Collective Actions in Europe A Comparative, Economic and Transsystemic Analysis. - Nagy, Csongor István (SpringerBriefs in Law, 2019)
This open access book offers an analytical presentation of how Europe has created its own version of collective actions. In the last three decades, Europe has seen a remarkable proliferation of collective action legislation, making class actions the most successful export product of the American legal scholarship. While its spread has been surrounded by distrust and suspiciousness, today more than half of the EU Member States have introduced collective actions for damages and from those who did, more than half chose, to some extent, the opt-out system. This book demonstrates why collective actions have been felt needed from the perspective of access to justice and effectiveness of law, the European debate and the deep layers of the European reaction and resistance, revealing how the Copernican turn of class actions questions the fundamentals of the European thinking about market and public interest. Using a transsystemic presentation of the European national models, it analyzes the way collective actions were accommodated with the European regulatory environment, the novel and peculiar regulatory questions they had to address and how and why they work differently on this side of the Atlantic.